Development and evaluation of home-made ball-on ring and ball on disk devices - Seré, Pablo Ricardo (2019)
The electrochemical deposition of metals and alloyshas been used for over 100 years, mainly withdecorative purposes. However, this technique haslately been employed to obtain functional coatingswith excellent mechanical and tribological properties[1,2]. As a result, determination of wear resistanceand coefficient of friction (CoF) of has become ofgreat interest for the both academic and industrialresearchers in the field of electroplating.Nevertheless, no measuring devices were available inLa Plata?s region making evaluation of large numbersof samples difficult or time consuming. For thisreason, both a ball-on-disk and a ball-on-ringmeasuring setup were designed and constructedtogether with the data recording and processingdevice. The present manuscript presents the details ofthe equipment developed together with somepreliminary results performed on well-characterizedmaterials to assess the reliability of these home-madesystems.